2016
DOI: 10.1038/nn.4423
|View full text |Cite
|
Sign up to set email alerts
|

Gravity orientation tuning in macaque anterior thalamus

Abstract: Gravity may provide a ubiquitous allocentric reference to the brain’s spatial orientation circuits. Here we describe neurons in the macaque anterior thalamus tuned to pitch and roll orientation relative to gravity, independent of visual landmarks. We show that individual cells exhibit two-dimensional tuning curves, with peak firing rates at a preferred vertical orientation. These results identify a thalamic pathway for gravity cues to influence perception, action and spatial cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 15 publications
(19 reference statements)
13
71
0
Order By: Relevance
“…It is also possible that vertical information might be more evident in the thalamus if we studied navigation in a real environment instead of a virtual environment. Recently, Laurens, Kim, Dickman, and Angelaki () found cells tuned to gravity (vertical tilt) in the macaque anterior thalamus using a rotatable apparatus (Laurens et al, ). Even though the pre‐scan immersive training and the optic flow during our scanning experiment could have enhanced the HD signal, physical head tilt and acceleration was missing in our fMRI study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that vertical information might be more evident in the thalamus if we studied navigation in a real environment instead of a virtual environment. Recently, Laurens, Kim, Dickman, and Angelaki () found cells tuned to gravity (vertical tilt) in the macaque anterior thalamus using a rotatable apparatus (Laurens et al, ). Even though the pre‐scan immersive training and the optic flow during our scanning experiment could have enhanced the HD signal, physical head tilt and acceleration was missing in our fMRI study.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that vertical information might be more evident in the thalamus if we studied navigation in a real environment instead of a virtual environment. Recently, Laurens, Kim, Dickman, and Angelaki (2016) found cells tuned to gravity (vertical tilt) in the macaque anterior thalamus using a rotatable apparatus (Laurens et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that directional tuning was relatively normal in the initial trial suggests that otolith signals are not crucial for the directional tuning of head direction cells but, instead, contribute to the maintenance of directional tuning across changes in vertical orientation. However, it is also possible that the activity of rodent head direction cells is directly influenced by gravity, given the recent discovery of gravity-sensitive neurons in the primate anterior thalamus [46]. Further, it is important to consider the role of linear movements in path integration, given that the acceleration phase of linear movements would be detected by the otolith organs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, SVV tasks engage temporo-parietal-insular cortices (Fiori et al 2015;Kheradmand & Winnick 2017), although temporal and spatial processing of gravity may not necessarily co-localize in the same regions (Maffei et al 2016). J Physiol 597.7 Detailed electrophysiological studies in monkeys have shown that neurons carrying signals of head and body orientation relative to gravity, independent of visual landmarks, can be found in several brain regions, including the brainstem, cerebellum, thalamus, temporal, parietal and insular cortices (Angelaki et al 2004;Chen et al 2011;Laurens et al 2013Laurens et al , 2016. Several of these neurons use internal models of physics to disentangle gravitoinertial cues (Angelaki et al 2004) or visual motion cues for target interception (Cerminara et al 2009;Streng et al 2018).…”
Section: Putative Neural Substratesmentioning
confidence: 99%